Oxford reading tree come in fro pre-primary - Hunt Roderick (Karachi; Oxford Uniersity Press, 2012)
The Stage 4 Biff, Chip and Kipper stories provide a rich story context to help develop language comprehension and decoding skills. Stories, More Stories A, More Stories B and More Stories C help children to progress from teacher-supported reading at the early stages to more independent reading
Keywords: Readers (Elementary)